Smarter than humans? Validating how OpenAI's ChatGPT model explains crowdfunding, alternative finance and community finance - Karsten Wenzlaff; Sebastian Spaeth (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2022)
The ChatGPT model of OpenAI allows users to ask questions, which are answered through an artificial intelligence trained through supervised, reinforced machine-learning. The answers depend on the input which the algorithm receives from the users, as well as from the content it has been given. The paper explores how answers to definitions about crowdfunding, alternative finance and community finance deviate or correspond to answers given by real human-beings in academic scholarship. Crowdfunding, alternative finance and community finance are chosen because academic literature does not provide consistent definitions on each of these terms, but some definitions are accepted by more scholars. By addressing the research gap concerning the accuracy of answers generated by an artificial intelligence, the paper contributes to the growing literature of implications of textual artificial intelligence on academia.
Keywords: 330; Crowdfunding; Alternative Finance; Community Finance; Machine Learning; Artificial Intelligence